Inovasi Pendidikan Infak Dalam Pengembangan Multiple Intellegences Siswa RA Al Fitroh Kabupaten Jember - Ellyda Setya Rini; Nita Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Religious based education at Raudhatul Athfal level is often carried out routinely without being structured as a planned and integrated learning process. This study aims to describe the renewal form of the infak education program and its implementation in developing various intelligence potentials of children aged 5–6 years at RA Al‑Fitroh, Jember Regency. This research employed a descriptive qualitative approach to portray the actual conditions in the field. Data were collected through participatory observation, in‑depth interviews with school principals, teachers, parents, and students, as well as documentation review. Data validity was ensured using source and method triangulation techniques. The results reveal that infak activities have been comprehensively renewed into a planned, creative, and engaging learning medium,rather than merely a routine religious practice. Innovations include diverse learning methods, attractive educational media, and active child participation throughout the activities. The program’s implementation proved effective in stimulating integrated development of language, logical‑mathematical, physical‑motor, and spatial abilities, while also strengthening social awareness, religious values, responsibility, and independence from early childhood. These findings serve as a reference for developing religious‑based learning that is fully integrated with children’s holistic development in similar educational institutions.